2003
DOI: 10.1073/pnas.0932692100
|View full text |Cite
|
Sign up to set email alerts
|

Repeated observation of breast tumor subtypes in independent gene expression data sets

Abstract: Characteristic patterns of gene expression measured by DNA microarrays have been used to classify tumors into clinically relevant subgroups. In this study, we have refined the previously defined subtypes of breast tumors that could be distinguished by their distinct patterns of gene expression. A total of 115 malignant breast tumors were analyzed by hierarchical clustering based on patterns of expression of 534 ''intrinsic'' genes and shown to subdivide into one basal-like, one ERBB2-overexpressing, two lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

151
4,300
21
145

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 4,691 publications
(4,617 citation statements)
references
References 25 publications
151
4,300
21
145
Order By: Relevance
“…To perform this analysis, we leveraged four large patient cohorts with accompanying gene expression profiling data from studies of breast cancer patients with extensive clinical follow-up. These represent four of the largest data sets in the public domain in which microarray profiles and long-term patient outcomes are available: (i) 103 patients from the Norway/Stanford study of response to chemotherapy of locally advanced cancer (33); (ii) 295 consecutive breast cancer patients from the Netherlands Cancer Institute (NKI) (34); (iii) 251 consecutive breast cancer patients from Uppsala, Sweden (35); and (iv) 159 surgically resected breast cancer patients from the Karolinska Institute in Stockholm, Sweden (31). Patient outcomes measured in these studies were either disease-specific survival (DSS) (death due to breast cancer) or distant metastasis–free survival (DMFS) (recurrence of cancer at a distant organ site).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To perform this analysis, we leveraged four large patient cohorts with accompanying gene expression profiling data from studies of breast cancer patients with extensive clinical follow-up. These represent four of the largest data sets in the public domain in which microarray profiles and long-term patient outcomes are available: (i) 103 patients from the Norway/Stanford study of response to chemotherapy of locally advanced cancer (33); (ii) 295 consecutive breast cancer patients from the Netherlands Cancer Institute (NKI) (34); (iii) 251 consecutive breast cancer patients from Uppsala, Sweden (35); and (iv) 159 surgically resected breast cancer patients from the Karolinska Institute in Stockholm, Sweden (31). Patient outcomes measured in these studies were either disease-specific survival (DSS) (death due to breast cancer) or distant metastasis–free survival (DMFS) (recurrence of cancer at a distant organ site).…”
Section: Resultsmentioning
confidence: 99%
“…Correlations between ferroportin expression in primary breast tumors and metastatic recurrence in patients were assessed with gene expression profiles from publicly accessible microarray data sets: (i) the Norway/Stanford study (33) (http://genome-www.stanford.edu/breast_cancer/mopo_clinical/data.shtml), (ii) the NKI study (34) (http://www.rii. com/publications/2002/nejm.html), (iii) the Uppsala study (35) [Gene Expression Omnibus (GEO) accession number GSE3494], and (iv) the Stockholm study (31) (GEO accession number GSE1456).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] As the recognition of the different epithelial phenotypes become more widespread, tailored therapeutic strategies may become more important.…”
mentioning
confidence: 99%
“…initially proposed a molecular classification for breast cancer. Using a cDNA microarray of 38 breast cancer cases, this group defined a list of intrinsic genes 27, 28. Moreover, a larger cohort of breast cancer patients revealed that the luminal subgroup may be divided into luminal A and B 29.…”
Section: Discussionmentioning
confidence: 99%